Propagation of Activated B Cells by In Vitro Severe Fever With Thrombocytopenia Syndrome Virus Infection of Human Peripheral Blood Mononuclear Cells. (5th July 2021) - Wada, Yuji; Miyamoto, Sho; Iida, Shun; Sano, Kaori; Sato, Yuko; Ainai, Akira; Saito, Kumpei; Katano, Harutaka; Hasegawa, Hideki; Suzuki, Tadaki
Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging, life-threatening tick-borne viral hemorrhagic fever caused by SFTS virus (SFTSV). Transient appearance of plasmablastic lymphocytes in the peripheral blood of SFTS cases has been reported; however, the pathological significance of this transient burst in peripheral blood plasmablastic lymphocytes is unclear. Here, we show that SFTSV infection of human peripheral blood mononuclear cells in vitro induced propagation of atypical lymphocytes. These atypical lymphocytes were activated B cells, which were induced by secretory factors other than viral particles; these factors were secreted by SFTSV-infected B cells. Activated B cells shared morphological and immunophenotypic characteristics with B cells of plasmablast lineage observed in peripheral blood and autopsy tissues of SFTS cases. This suggests that SFTSV-infected B cells secrete factors that induce B-cell differentiation to plasmablasts, which may play an important role in pathogenesis of SFTS through the SFTSV-B cell axis. Abstract : In vitro infection of human PBMCs with a tick-borne hemorrhagic fever virus, SFTSV, stimulates propagation of activated B cells, which mimic the virus target cells observed in SFTS patients, and are induced by secretory factors produced from B cells themselves.